TOXIC MASCULINITY DALAM SISTEM PATRIARKI (Analisis Wacana Kritis Van Dijk Dalam Film “Posesif”) - Desvira Jufanny; Lasmery R.M. Girsang (Universitas Bunda Mulia, 2020)
ABSTRACTPatriarchy is defined as positioning the man as the center or central, sole authority. This qualitative research based on critical paradigm analyzes discourses inside the film